Language as cultural expression: An anthropolinguistics study of Javanese mantra in the traditional ceremony Malam 1 Sura - Seishaditha Aleyda Prasetya; Ajar Pradika Ananta Tur; Simon Ntamwana; Iriana Ilgizovitch Alexandrovna (Universitas Ahmad Dahlan, 2026)
The symbolic role of mantra language in Javanese ritual traditions remains understudied, particularly in the macapat sung during the Malam 1 Suro ceremony at the Ngayogyakarta Hadiningrat Palace. This study examines the symbolic functions of macapat as ritual mantra performed by palace courtiers. Employing a qualitative descriptive approach, data were gathered through organizational access, observation, interviews, document and audio-visual analysis, and ethical practice. Interviews with KRT. Rintaiswara and KRT. Kusumonegoro were triangulated with information from R.Ngt. Kingkin of the Yogyakarta Cultural Office to ensure validity. Findings show that the macapat recited in the ceremony serves as a safety-seeking mantra whose linguistic form has evolved into a blend of Old Javanese, modern Javanese, and everyday language. The analysis identifies four symbolic functions shaping ritual communication: (a) tradition as microphysics of power, (b) language as a symbolic enactment of belief systems, (c) language as soulful resonance, and (d) language as an identity marker of Yogyakarta’s governance. This research contributes to linguistic anthropology and ritual discourse studies by demonstrating how macapat functions not merely as verbal expression but as a symbolic medium embodying socio-cultural, spiritual, and political meanings within Javanese court practice.